Managing Global Sourcing: Inventory Performance - Jain, Nitish; Girotra, Karan; Netessine, Serguei (Management Science, 2014)
The use of global suppliers has increased considerably over the last three decades. Operations management theory establishes that global sourcing requires more units of inventory, but since these units are often procured at a lower cost from global suppliers the capital invested in inventory and the consequent financial burden may increase or decrease with global sourcing. This study provides rigorous firm-level empirical evidence that links the global sourcing practices of public U.S. firms and their inventory investments. We process bill of lading manifests (customs forms) to extract information on over half a million sea shipments from global suppliers to U.S. public firms and link this information with quarterly financial data from the Compustat database. We provide stylized facts on the participation of different firms and sectors in global trade. Using a simultaneous equation model, we find that an increase in global sourcing results in an increase in inventory investment. A 10% shift in sourcing from domestic to global suppliers increases the inventory investment by 8.8% for an average firm in our sample. We also find that increasing the number of suppliers can mitigate this increase in inventory investment: for example, going from single to dual sourcing reduces inventory investment by about 11%. We illustrate the use of our estimates to identify the impact of changing global sourcing strategy on inventory investment and operational performance metrics. This paper was accepted by Martin Lariviere, operations management.